The Development of Disruptive Organizations and Technologies - Espinoza, Sofía Genoveva Rivera; Ocampo, Patricia Sotelo; Ángel, Carlos Enrique Martínez del (Journal of Ecohumanism, 2024)
Technological innovations usually have an impact on society by marking notable and lasting changes, generating advances that transform the social visa, this type of technologies better known as disruptive that provide a potential being reflected in the activities of the business environment obtaining greater opportunities in the market; where the organization can better adapt to globalization to stand out from the competition seeking to manage tasks in an agile and Simple. Although technological transformations increase productivity and/or profitability, each company has different needs, but the purpose of most is to manage processes. The development of this work allows us to identify the advantages of disruptive technologies which break the established schemes, defining new ways of solving business needs for a comprehensive improvement where business environments transform the way of doing business by improving the performance of tasks by the operational level, offering great advantages and opportunities for growth applying a series of particularities of the field innovative.